Color stability of polycarbonate for optical applications. (October 2015) - de Brouwer, Hans; van den Bogerd, Jos; Hoover, James
Graphical abstract: Highlights: Polycarbonate color stability investigated through spiking experiments. Main drivers for polycarbonate yellowing through time are BPA monomer impurities. Proposed degradation scheme explains color effects quantitatively. Abstract: Poly(bisphenol A carbonate) or polycarbonate has excellent mechanical properties which, combined with its inherent transparency, makes it the material of choice for lighting applications such as lenses, light guides and bulbs but also for construction of roofing, greenhouses and verandas. With the advent of LED technology, the functional lifetime of lighting products has increased impressively and will further expand in the years to come. Also in construction applications, durability is key. Plastics will age though under the influence of heat, light and time, causing reduced light transmission and color changes. In this paper, we will indicate several key factors that determine the optical material performance and show how detrimental two specific monomer impurities are on the color performance of the resulting plastic over time.